Kinerja dan Pengaruh Fender Dermaga 05B dan 05C Terminal Ciwandan Pelabuhan Banten - Dinda Devita (Jurnal Teknik Transportasi, 2023)
Operational performance of piers 05B and 05C in loading and unloading services dry bulk and general cargo in the Ciwandan Terminal of Port of Banten is not yet optimal. There are many contributing factors, including the use of inappropriate fenders. Therefore this research was conducted to analyze the operational performance of pier and effect of fender to that performance. The research method is quantitative using secondary data. The service fluency is measured through ship service performance indicators (waiting time, approach time, effective time and berthing time), loading and unloading services T/G/H (Ton/Gang/Hour), BOR (berth occupancy ratio), then associated with the effect of use fender. The analysis results show that performance of pier 05B and 05C on waiting time value is not good more than 1 hour, approach time good enough under 1 hour, ET:BT values ​​76.01% and 76.14% close to standard (80%), T/G/H values dry bulk not good and general cargo good, BOR is below standard (< 70%), with suggested improvement waiting time, T/G/H and BOR. Analysis condition of fender that not according to pier conditions, and it is recommended to use fenders type cone SCN-1000H F1.1. Analysis of mooring energy are 385 kNm and the horizontal force is 647Kn, so distance between fenders is suggested to be 8-12 meters.